Reinterpreting good and evil in fantasy: A case study on His Dark Materials and Good Omens - Sattarujawong, Yada (Humanities, Arts and Social Sciences Studies, 2025)
The contrast between good and evil is a widely recognized characteristic of fantasy fiction. The growing number and influence of religious references and creative interpretations in fantasy literature indicate the need to analyze the distinction between good and evil that is often present in these works. The literary works chosen for this study are Good Omens (1990) by Pratchett and Gaiman, and Pullman’s His Dark Materials trilogy, consisting of Northern Lights (1996), Subtle Knife (1998), and Amber Spyglass (2001). These two works examine the reinterpretation of the fall and the judgment day. These works review, mock, and challenge religious figures such as God, angels, and demons as well as the conventional understanding of good and evil. This study examines how the two works depict the author's distinct perspective, the protagonist's journey, and their challenge to the concept of moral standards. The religious allusions in these works comprise the portrayal of changing ideas and the interpretation of the absolute good and evil binary in fantasy literature. Therefore, our approval of the new version of evilness and its development entails more than just instructing children to differentiate superficially between what is morally correct and incorrect. The intricate portrayal of evilness in fantasy literature aimed at children could greatly enhance their ability to comprehend and integrate the multifaceted nature of human circumstances, hence fostering their cognitive growth.